Enhancement of the Interlayer Interaction between Polystyrene and Polyvinyl Alcohol by Ozone Treatment - Lin Su; Jie Li; Jing Li; Qiaomei Chu; Bo Li; Yiyang Liu (Advances in Polymer Technology)
The ozonization modification of polystyrene (PS) was conducted in acidic condition to enhance the interfacial interaction between PS and polyvinyl alcohol (PVA). Infrared spectra results revealed that the carbonyl and hydroxyl groups were successfully introduced to the PS film by ozonization. The hydrophobic PS was turned to be hydrophilic to some extent by contact angle experiment, which led to the enhancement of interfacial adhesion between PS and PVA. In addition, the adsorption of PS to PVA was also improved. Nano indenter measurement indicated the interfacial interaction between PS film and PVA film was obviously enhanced by 40% after ozonization at room temperature for 2 h in acidic condition, which will benefit for fabricating laser inertial confinement fusion container.